Knowledge, attitude and response of mothers about fever in their children. Issue 12 (8th December 2011) - Arica, Seçil Gunher; Arica, Vefik; Onur, Hatice; Gülbayzar, Sayat; Dağ, Hüseyin; Obut, Ömer
Abstract : Aim: This study was conducted to determine mothers' knowledge about fever, and their attitudes and responses to fever in children, along with the influence of demographic characteristics on the level of knowledge, and to identify occurrences of fear of fever. Materials and Methods: The study consisted of 4500 mothers with children 0–12 years of age who were referred to the pediatric health and disease polyclinic and primary care polyclinic over a period of 24 months. Data were collected using a questionnaire containing 32 open-ended, multichoice questions, and assessed using number, percentage and χ 2 analyses. Results: In this study, 36% of mothers regarded body temperatures lower than 37°C as fever; 83% believed that fever was harmful for their children, and 92.3% experienced fear and concern due to their child's fever. The most significant reason for fear was the belief that the child may have a seizure. Moreover, 12% of mothers feared that their child would die due to fever. The level of fear triggered by fever was lower as the education level of the mothers increased. Meanwhile, when their child had a fever, 28.9% of mothers used antifebrile drugs without consulting a physician, while 19% applied cold water and 7.7% applied water with alcohol or vinegar, among other inappropriate practices. Conclusion: Increased information about fevers geared towards the caregivers of children, particularly mothers, would prevent the unnecessary treatment of children, as well as minimising delayed and insufficient responses to fever.